Sulfinamide Synthesis Using Organometallic Reagents, DABSO, and Amines - Lo, Pui Kin Tony (J Org Chem, 2020)
[Image: see text] We report the synthesis of sulfinamides using organometallic reagents, a sulfur dioxide reagent, and nitrogen based-nucleophiles. The addition of an organometallic reagent to the commercially available sulfur dioxide surrogate, DABSO, generates a metal sulfinate which is reacted with thionyl chloride to form a sulfinyl chloride intermediate. Trapping the sulfinyl chlorides in situ with a variety of nitrogen nucleophiles delivers sulfinamides in 32–83% yields. Each stage of the process is performed at room temperature, and the total reaction time is only 1.5 h.